Development of an Integrating Sphere-Based Wide-Range Light Source System for the Linearity Evaluation of a Photodetector Used in Radiation Detection and Bioanalysis Instruments - Tetsuro Matsumoto; Akihiko Masuda; Minoru Tanabe; Seiya Manabe; Hideki Harano; Kazuki Niwa (Sensors)
We developed a compact wide-range light source system for evaluating the linearity of photomultiplier tube (PMT) output. This system utilizes two integrating spheres equipped with a continuously variable slit and output aperture to modulate a stabilized light-emitting diode light source, producing an output light range as wide as seven orders of magnitude. To verify the wide linearity range of the integrating sphere system, three silicon photodiodes coupled with electric current readers monitored the light intensity and simultaneously confirmed each other’s linearity. Using this system, we evaluated the linearity of the PMT used in a neutron detector we are currently developing and found it to have a linear range of more than four orders of magnitude. Non-linearity characteristics were also successfully measured in detail at a higher output range. Neutron detector operation requires both calibration of the detection efficiency and evaluation of the linearity between the neutron dose and its output. These results indicate that this system is a simple and useful method to evaluate the linearity of photodetectors used in radiation detectors and other applications.